Perancangan Spreader bar sebagai Alat Bantu Pengangkatan pada Proses Erection - Isna Dewi Assa Ashariyani; Pranowo Sidi; Priyambodo Nur Ardi Nugroho (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
The lifting process is needed, among other things, to move goods and maintain the position of the equipment. In this lifting process, spreader bars are needed because the size of the equipment being lifted is too large, but the sling must not hit the equipment. This spreader bar will work with high intensity due to repeated or cyclical load treatment, so fatigue in the structure is likely to occur. Thus, it is necessary to analyze the strength of the structure and estimate the life of the spreader bar. The design method used is the Ulrich method, which involves creating three design concepts from which the best design will be selected according to the selection criteria. Modeling is done with Fusion 360 software, and strength and fatigue life analysis is done using ANSYS Workbench 2023 R1 software with the aim of knowing the amount of stress from the loading received by the structure. The strength analysis of the spreader bar structure in the selected design concept obtained a maximum stress value of 154.71 MPa; this value is still at a safe limit because it is below the maximum allowable stress value of 166.667 MPa, and the safety factor obtained is 5.6026. This value is safe because it is greater than 1. The total estimated material cost required for this spreader bar is IDR 21,866,910.67.